1992
DOI: 10.1021/bi00151a015
|View full text |Cite
|
Sign up to set email alerts
|

Segmental motion in catalysis: investigation of a hydrogen bond critical for loop closure in the reaction of triosephosphate isomerase

Abstract: A residue essential for proper closure of the active-site loop in the reaction catalyzed by triosephosphate isomerase is tyrosine-208, the hydroxyl group of which forms a hydrogen bond with the amide nitrogen of alanine-176, a component of the loop. Both residues are conserved, and mutagenesis of the tyrosine to phenylalanine results in a 2000-fold drop in the catalytic activity (kcat/Km) of the enzyme compared to the wild-type isomerase. The nature of the closure process has been elucidated from both viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
119
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 28 publications
8
119
1
Order By: Relevance
“…Later experiments suggested that the loop closes after the Michaelis complex is formed, rather than as it is formed (Sampson & Knowles, 1992). This observation is consistent with the paradigm for enzymatic catalysis: that stabilization of intermediates and transition states should be favored over stabilization of substrates and products.…”
supporting
confidence: 66%
“…Later experiments suggested that the loop closes after the Michaelis complex is formed, rather than as it is formed (Sampson & Knowles, 1992). This observation is consistent with the paradigm for enzymatic catalysis: that stabilization of intermediates and transition states should be favored over stabilization of substrates and products.…”
supporting
confidence: 66%
“…Metabolically, this would have dire consequences by decoupling OAA consumption from PEP synthesis. A similar function has been ascribed to the active site lid domain in TIM, which is thought to sequester the intermediate of that reaction, preventing its hydration, which would lead to the toxic side product methylglyoxal (25,26). Thus, our model for PEPCK catalysis suggests a mechanism by which the closed conformation of the enzyme becomes increasingly thermodynamically favorable as the enzyme progresses along the reaction coordinate.…”
Section: Induced Fit and Conformational Selectionsupporting
confidence: 53%
“…This results in the occlusion of the active site from the bulk solvent (20)(21)(22)(23)(24). These conformational changes, often required to preclude solvent from competing with the catalzyed reaction (25,26), also preclude substrate binding directly to this enzyme form. Therefore, even if we assume that the lowly populated ''active'' form of the conformational selection model is the same as the ''key-lock'' state and that the enzyme samples this state in solution, then substrate cannot bind directly to this state due to steric occlusion of the active site [supporting information (SI) Fig.…”
mentioning
confidence: 99%
“…A different behavior on viscosity has been found for rate-determining events involving diffusion-controlled motions of enzyme portions. As this is an intramolecular event, plots of k cat°/ k cat against /°usually display slopes Ͻ1 because the solvent viscosity effect is damped by an internal friction of protein regions (15). Clearly, the effect of viscosogen on k cat may vary depending on its accessibility and then on its molecular hindrance.…”
Section: A Physical Process Is the Rate-limitingmentioning
confidence: 99%